Determinantes de la intención emprendedora de los habitantes de la ciudad de Puyo - Simba Fustillos, Tamara Lizbeth (2025)
The objective of this research was to identify the determining factors of entrepreneurial intention among residents of Puyo City. To this end, a quantitative, non-experimental, and cross-sectional approach was used, administering a questionnaire to a sample of 374 people from the economically active population. Data analysis was performed using Logit and Probit econometric models to examine the relationship between entrepreneurial intention and variables including self-efficacy, attitude, subjective norm, and sociodemographic factors. The results revealed a predominantly 15- to 35-year-old respondent profile with a high level of education. A high entrepreneurial intention was found, driven primarily by the desire for autonomy ("being one's own boss") and innovation. Immediate family members were found to be the main source of perceived social support. The econometric analysis concluded that the most significant determinants of entrepreneurial intention are self-efficacy (confidence in one's own abilities to undertake a business) and attitude (a positive assessment of entrepreneurship). In contrast, subjective norm (social pressure), educational level, age, or number of children were not statistically significant factors. This suggests that entrepreneurship-promotion policies in Puyo should focus on strengthening the competencies and personal confidence of potential entrepreneurs rather than on contextual factors.